Barriers to husbands' involvement in maternal health care in Sidama zone, Southern Ethiopia: a qualitative study - Wondwosen Teklesilasie; Wakgari Deressa (BMC, 2020)
Abstract Background Husbands' involvement in maternal care is considered as a crucial step in scaling up women's utilization of the services. However, the factors related with how husband's involvement in maternal health care have hardly been studied to date in the study areas. Therefore, this study aimed to explore barriers to husbands' involvement in maternal health care, in Sidama zone, Southern Ethiopia. Methods The study employed a qualitative method. A pre-tested interview guide questions that prepared in English and translated in to Amharic language were used for data collection. The data were collected using focus group discussions, in-depth interviews and key-informants' interview in April and May 2015. The data were analyzed thematically. Results The study identified a range of factors that-deterred husbands to involve in their female partners' maternal health care. These are childbirth is a natural process, pregnancy and childbirth are women's business, preference for TBAs' care and husband's involvement in pregnancy and birth care is a new idea were identified as barriers for husbands' involvement in maternal health care, in this study. Conclusions A range of factors related with clients' and service delivery factors' were identified as barriers to husbands' involvement in maternal health care. Based on the study findings we recommend a contextual based awareness creation programs about husbands' involvement in maternal health care need to be established.